2014
DOI: 10.1016/j.mib.2014.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial sensing of bacteriophages in communities: the search for the Rosetta stone

Abstract: Billions of years of evolution have resulted in microbial viruses and their hosts communicating in such a way that neither of these antagonists can dominate the other definitively. Studies of the molecular mechanisms underlying this dialog, initially in bacteriophages, rapidly identified several of the ways in which bacteria resist bacteriophage infections and bacteriophages defeat bacterial defenses. From an ecological perspective, recent data have raised many questions about the dynamic interactions between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…23,24,45 This is not surprising as bacteriophages are the most abundant viruses present in the human GIT, being part of our natural microbiota, and are far more abundant than viruses infecting eukaryotic cells. 46,47 Recent virome studies on samples from IBD patients showed that the microbiota of these patients displayed an altered bacteriophage composition, raising questions about the possible role of these viruses in the disease. 48 Most of the bacteriophages detected were temperate [as opposed to virulent], suggesting a putative role in dynamic interactions between bacteria possibly leading to genetic exchanges.…”
Section: Discussionmentioning
confidence: 99%
“…23,24,45 This is not surprising as bacteriophages are the most abundant viruses present in the human GIT, being part of our natural microbiota, and are far more abundant than viruses infecting eukaryotic cells. 46,47 Recent virome studies on samples from IBD patients showed that the microbiota of these patients displayed an altered bacteriophage composition, raising questions about the possible role of these viruses in the disease. 48 Most of the bacteriophages detected were temperate [as opposed to virulent], suggesting a putative role in dynamic interactions between bacteria possibly leading to genetic exchanges.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, as many studies link microbiota composition to human diseases/disorders, we can envisage the use of bacteriophages to gently manipulate this microbiota composition to maintain an environment favoring human health (Nicholson et al, 2012;Norman et al, 2015;Parekh et al, 2015;Sampson and Mazmanian, 2015). Therefore, given the current 'phage therapy 2.0' stage, with implementation of clinical trials and synthetic biology approaches, research should now engage in 'phage therapy 3.0' by taking into consideration a third partner, the eukaryotic cell (epithelial or immune) (Debarbieux, 2014;Young and Gill, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It is currently estimated that 60–70% of known bacterial genomes contain prophages , a number that is likely to increase as novel phages are sequenced. These prophages are not passive, but rather, they are active participants in shaping the bacterial community composition and biogeography, which in turn have an effect on the human host and its immune system [72, 7476]. …”
Section: The Human Oral Viromementioning
confidence: 99%